An Asymmetric Chromosome Pair Undergoes Synaptic Adjustment and Crossover Redistribution During Caenorhabditis elegans Meiosis: Implications for Sex Chromosome Evolution - Henzel, Jonathan V. (Genetics Society of America, 2011)
Heteromorphic sex chromosomes, such as the X/Y pair in mammals, differ in size and DNA sequence yet function as homologs during meiosis; this bivalent asymmetry presents special challenges for meiotic completion. In Caenorhabditis elegans males carrying mnT12, an X;IV fusion chromosome, mnT12 and IV form an asymmetric bivalent: chromosome IV sequences are capable of pairing and synapsis, while the contiguous X portion of mnT12 lacks a homologous pairing partner. Here, we investigate the meiotic behavior of this asymmetric neo-X/Y chromosome pair in C. elegans. Through immunolocalization of the axis component HIM-3, we demonstrate that the unpaired X axis has a distinct, coiled morphology while synapsed axes are linear and extended. By showing that loci at the fusion-proximal end of IV become unpaired while remaining synapsed as pachytene progresses, we directly demonstrate the occurrence of synaptic adjustment in this organism. We further demonstrate that meiotic crossover distribution is markedly altered in males with the asymmetric mnT12/+ bivalent relative to controls, resulting in greatly reduced crossover formation near the X;IV fusion point and elevated crossovers at the distal end of the bivalent. In effect, the distal end of the bivalent acts as a neo-pseudoautosomal region in these males. We discuss implications of these findings for mechanisms that ensure crossover formation during meiosis. Furthermore, we propose that redistribution of crossovers triggered by bivalent asymmetry may be an important driving force in sex chromosome evolution.